Students’ Listening Competence Through English Recorded Materials in the English Education Study Program at Lakidende University - Iin Wahyudi (Indo Green Journal, 2026)
Listening is the foundational receptive skill in language acquisition, yet it remains the most challenging competency for English as a Foreign Language (EFL) learners, especially in regional contexts with limited exposure to authentic English environments. This study aims to examine students’ listening competence before and after intervention using English recorded materials, measure the significance of improvement, and analyze students’ perceptions toward this learning media. A convergent parallel mixed‑methods design was employed, combining a quasi‑experimental one‑group pre‑test post‑test approach with descriptive qualitative analysis. The participants were 22 fifth‑semester students selected through purposive sampling from the English Education Study Program at Lakidende University. Data were collected using validated listening tests, questionnaires, and semi‑structured interviews over an 8‑week intervention period. Quantitative data were analyzed via descriptive statistics and paired‑samples t‑test, while qualitative data were processed through thematic analysis. Results showed that: (1) Pre‑intervention listening competence was predominantly Fair with a mean score of 58.7; (2) Post‑intervention mean score increased to 74.2 (Good category), with improvement statistically significant at p < 0.001; (3) Students positively perceived repeatability, adjustable speed, and authentic exposure as key advantages, while unstable internet and limited vocabulary were main challenges. The findings confirm that structured use of English recorded materials effectively enhances listening competence and is suitable for EFL instruction in resource‑limited regional areas.